Rediscovery of Chamaesyce sebastinei (Binojk. & N.P. Balakr.) V.S. Raju (Angiosperms: Euphorbiaceae) a little-known rare species from Andhra Pradesh, India - C.S. Reddy; S.M.M. Javed; F. Tampal; C. Pattanaik; V.S. Raju (Journal of Threatened Taxa, 2010)
Chamaesyce sebastinei (Binojk. & N.P. Balakr.) V.S. Raju of Euphorbiaceae, an endemic species, is recollected after 50 years from its type locality in Andhra Pradesh, India.